Al-Manhaj At-Tarbawi Al-Islami Fi Ta'limi Din Al-Islam (Dirasah Tahliliyah Muqaranah Baina Fikrati Ash-Syaikh Muhammad Mutawaly Ash-Sharawy wa As-Sayyid Muhammad bin Al-Alawy Al-Maliki). - Ahmad bin Hamid Alawi Assaquf (Jurnal Hikmatuna, 2016)
The Islamic society in this era is in dire need of an Islamic educational approach in teaching the religion of Islam. This is necessary for the survival of the leading Islamic civilization among the civilizations of nations around the world. It is important to guide the younger generation through the education of Islam towards their own well-being and the well-being of their society. The weaknesses and lack of progress experienced by the Islamic nation, unlike other nations, call for a return and an exploration of the correct understanding in the Islamic educational approach, following the example of the righteous predecessors, especially in the process of teaching the religion of Islam. This is considered an important attempt to consolidate the correct understanding of the Islamic educational approach in teaching the religion of Islam, which traces its roots back to the traditional Islamic school passed down from generation to generation. Among the late Islamic scholars who have a significant role in this field are Sheikh Muhammad Mutawaly Ash-Sharawy and Sayyid Muhammad bin Al-Alawy Al-Maliki. They both made significant efforts in explaining the Islamic educational approach in teaching the religion of Islam. Some of the questions they addressed include: What is Ash-Sharawy's idea regarding the Islamic educational approach in teaching the religion of Islam? What is Al-Maliki's idea regarding the Islamic educational approach in teaching the religion of Islam? What are the similarities and differences between the two ideas regarding the educational approach? What is Ash-Sharawy's idea and Al-Maliki's idea regarding the Islamic educational approach in teaching the religion of Islam? This research aims to understand both Ash-Sharawy's and Al-Maliki's perspectives on the Islamic educational approach in teaching the religion of Islam, analyzing and comparing them while highlighting their similarities and differences. Through a thorough understanding of this significant topic, it is concluded that the concept of the Islamic educational approach in teaching the religion of Islam encompasses ideas and concepts free from flaws, which are utilized to convey Islamic knowledge to learners in an accurate and easy manner, in line with a dignified life for individuals and the Islamic society. Ash-Sharawy and Al-Maliki both agree on the concept of nurturing in the field of education and that the Islamic educational approach in teaching the religion of Islam is divinely ordained and characterized by ease, righteousness, and perfection. However, Ash-Sharawy's idea regarding the Islamic educational approach in teaching the religion of Islam is more comprehensive than Al-Maliki's, and Al-Maliki provides a more detailed exploration of educational methods in his approach compared to Ash-Sharawy. Keywords: Islamic educational approach, teaching the religion of Islam, Ash-Sharawy's idea, Al-Maliki's idea.